The NuA4 Complex Promotes Translesion Synthesis (TLS)-Mediated DNA Damage Tolerance. Issue 4 (19th February 2015) - Renaud-Young, Margaret; Lloyd, David C; Chatfield-Reed, Kate; George, Iain; Chua, Gordon; Cobb, Jennifer
Abstract: Lesions in DNA can block replication fork progression, leading to its collapse and gross chromosomal rearrangements. To circumvent such outcomes, the DNA damage tolerance (DDT) pathway becomes engaged, allowing the replisome to bypass a lesion and complete S phase. Chromatin remodeling complexes have been implicated in the DDT pathways, and here we identify the NuA4 remodeler, which is a histone acetyltransferase, to function on the translesion synthesis (TLS) branch of DDT. Genetic analyses in Saccharomyces cerevisiae showed synergistic sensitivity to MMS when NuA4 alleles, esa1 -L254P and yng2 Δ, were combined with the error-free bypass mutant ubc13 Δ. The loss of viability was less pronounced when NuA4 complex mutants were disrupted in combination with error-prone /TLS factors, such as rev3 Δ, suggesting an epistatic relationship between NuA4 and error-prone bypass. Consistent with cellular viability measurements, replication profiles after exposure to MMS indicated that small regions of unreplicated DNA or damage were present to a greater extent in esa1 -L254P/ ubc13 Δ mutants, which persist beyond the completion of bulk replication compared to esa1 -L254P/ rev3 Δ. The critical role of NuA4 in error-prone bypass is functional even after the bulk of replication is complete. Underscoring this observation, when Yng2 expression is restricted specifically to G2/M of the cell cycle, viability and TLS-dependent mutagenesis rates were restored. Lastly, disruption of HTZ1, which is a target of NuA4, also resulted in mutagenic rates of reversion on level with esa1 -L254P and yng2 Δ mutants, indicating that the histone variant H2A.Z functions in vivo on the TLS branch of DDT.